TEACHING WRITING IN RECOUNT TEXT BY USING PLEASE STRATEGY TO THE HIGH SCHOOL STUDENTS - Imelda Noviani; Ridha Ilma (Jurnal Didascein Bahasa, 2018)
Writing is one of the four major skills and it is important because it needs a number of activities: setting goals, generating ideas, organizing information, selecting appropriate language, making a draft, reading and reviewing it, then revising and editing. The objective of the study was to find out whether or not there was any significant difference on students’ writing skill in recount text between the tenth grade students who were taught by using PLEASE strategy and those who were not. The population of the study was tenth grade students of SMAN 11 Palembang in the academic year 2016/2017. In doing the study, the writer did the experimental method by using quasi-experimental design to the two groups of students. The X IPA 5 class became the experimental group and the X IPS 2 became the control group. The two classes were chosen because they had the same level of competency in learning English. A test was the instrument for collecting the data. The test was administered twice, as the pre-test and post-test. The result showed that PLEASE strategy had a significant effect on the students’ writing skill. Keywords: writing skill, PLEASE Strategy.